2016
DOI: 10.1097/wco.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional MRI flow examinations in cerebral and extracerebral vessels – ready for clinical routine?

Abstract: Purpose of review To evaluate the feasibility of 4D flow MRI for the clinical assessment of cerebral and extracerebral vascular hemodynamics in patients with neurovascular disease. Recent findings 4D flow MRI has been applied in multiple studies to qualitatively and quantitatively study intracranial aneurysm blood flow for potential risk stratification and to assess treatment efficacy of various neurovascular lesions, including intra-aneurysmal and parent artery blood flow after flow diverter stent placement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 98 publications
4
60
0
Order By: Relevance
“…In another study, this technique was used to measure peak CSF flow at the craniocervical junction and cervical spinal canal in healthy individuals and those with Chiari malformations . However, while 4D flow MRI has shown great promise in understanding flow dynamics, long scan times (5‐20 min) and poor spatial resolution need to be addressed before it can be used as a routine clinical tool …”
Section: Discussionmentioning
confidence: 99%
“…In another study, this technique was used to measure peak CSF flow at the craniocervical junction and cervical spinal canal in healthy individuals and those with Chiari malformations . However, while 4D flow MRI has shown great promise in understanding flow dynamics, long scan times (5‐20 min) and poor spatial resolution need to be addressed before it can be used as a routine clinical tool …”
Section: Discussionmentioning
confidence: 99%
“…17,18 In addition to assessment of the flow velocity, the 4D flow MRI technique allows for the evaluation of several additional hemodynamic parameters that may be derived from the velocity information, such as wall shear stress (WSS), 6,19 blood pressure difference, 20 turbulence kinetic energy, 21 and viscous energy loss, 22 etc. Previous studies have demonstrated clinical applications of this technique for improved characterization of hemodynamics in neurovascular systems, 1,23,24 intraheart and great vessels, 25 and peripheral vessels. 26 The validity and accuracy of 4D flow MRI has been demonstrated using 2D PC MRI, Doppler ultrasound, or catheter as references.…”
mentioning
confidence: 99%
“…where l is the diffusivity scale of the ring's core; 1 I is the first-order modified Bessel function; 2F2 is the generalized hypergeometric function.…”
Section: Const Vmentioning
confidence: 99%
“…However, the lack of a gold standard reference in such conditions often limits the degree to which inferred flow measures can be trusted, regardless of whether the flow is derived from computational or image-based approaches. We propose a new reference for complex flow imaging in the form of the ring 1 Quality Control (QC) refers to "part of quality management focused on fulfilling quality requirements"-ISO 9000 clause 3.2.10. Quality Assurance (QA) refers to "a part of quality management focused on providing confidence that quality requirements will be fulfilled"-ISO 9000 clause 3.2.11.…”
mentioning
confidence: 99%
See 1 more Smart Citation